The barriers and benefits of implementing cloud computing in economic organizations - Kobis, Paweł; Chmielarz, Grzegorz (Business Informatics, 2017)
Information management in all types of organizations is nowadays directly connected with IT technologies implementation. Enterprises presently operating in global economy conditions are forced to take actions that increase their competitiveness and decrease the cost related to financing secondary activities, among others the functioning of IT departments. The dynamic development of cloud computing and services available in this model now constitutes an alternative for processing, storing and distributing information. The article presents selected aspects of the current stage of cloud computing development, possibilities of applying its services in economic organizations, with a particular consideration of the barriers and benefits that influence its implementation. Research concerning these features has been presented with the use of a new model of information management in enterprises in Poland and thorought the world
Informatyka Ekonomiczna = Business Informatics, 2017, Nr 3 (45), s. 66-79
Keywords: cloud computing; economic organization; IT technologies; data; information; chmura obliczeniowa; organizacja gospodarcza; technologie informatyczne; dane; informacja